Non-volatile toxic heavy metals analysis in surface water collected from Moon and Shi rivers in Northeastern of Thailand by atomic absorption spectrophotometry - Wongklom, Amornrat (Creative Science, 2016)
The concentrations of heavy metals such as Cd, Cr, Cu, Mn, Ni, Pb and Zn were investigated in surface water from Moon and Shi rivers, Northeastern of Thailand. Heavy metal concentrations were analysed by using atomic absorption spectrophotometer and compared with permissible limits set by World Health Organization. The concentrations of Cd (0.022-0.030 mg L-1) were higher than their respective permissible limits (0.003 mg L-1) in all samples, while Ni, Pb, Cu, Cr, Mn and Zn concentrations were observed within their respective limits. Mean concentrations of heavy metals in surface water samples were found in the order of Zn (0.178-0.286 mg/L) > Mn (0.035-0.199 mg L-1) > Ni (0.033-0.072 mg L-1) > Cd (0.024-0.030 mg L-1) > Cu (0.013-0.027 mg L-1) > Cr (BDL-0.020 mg L-1) > Pb (BDL), in the six locations of Moon river and Mn (0.117-0.409 mg L-1) > Zn (0.185-0.196 mg L-1) > Ni (0.028-0.112 mg L-1) > Cr (0.010-0.047 mg L-1) > Cd (0.022-0.027 mg L-1) > Cu (0.013-0.023 mg L-1) > Pb (BDL), in the four locations of Shi river. The geologic and anthropogenic activities were the possible sources of water contamination with heavy metals in the study area.